Association of β-Amyloid and Vascular Risk on Longitudinal Patterns of Brain Atrophy. (19th July 2022) - Rabin, Jennifer S.; Pruzin, Jeremy; Scott, Matthew; Yang, Hyun-Sik; Hampton, Olivia; Hsieh, Stephanie; Schultz, Aaron P.; Buckley, Rachel F.; Hedden, Trey; Rentz, Dorene; Johnson, Keith A.; Sperling, Reisa A.; et al.
Abstract : Background and objectives: Vascular risk factors and elevated β-amyloid (Aβ) are commonly observed together among older adults. Here, we examined the interactive vs independent effects of systemic vascular risk and Aβ burden on longitudinal gray matter atrophy and how their co-occurrence may be related to cognitive decline in a cohort of clinically normal adults. A secondary goal was to examine whether vascular risk influences gray matter atrophy independently from markers of white matter injury. Methods: Participants were 196 adults (age 73.8 ± 6.1 years) from the Harvard Aging Brain Study. Baseline Aβ burden was quantified with Pittsburgh compound B PET. Baseline vascular risk was measured with the Framingham Heart Study cardiovascular disease risk score. Brain atrophy was quantified longitudinally with structural MRI over a median of 4.50 (±1.26) years. Cognition was assessed yearly with the Preclinical Alzheimer Cognitive Composite over a median of 6.25 (±1.40) years. Linear mixed-effects models examined vascular risk and Aβ burden as interactive vs independent predictors of gray matter atrophy, with adjustment for age, sex, years of education, APOE ε4 status, intracranial volume (when appropriate), and their interactions with time. In subsequent models, we adjusted for markers of white matter injury to determine whether vascular risk accelerated brain atrophy independently from diffusion- and fluid-attenuated inversion recovery (FLAIR)–based markers. Mediation analyses examined whether brain atrophy mediated the interactive association of vascular risk and Aβ burden on cognitive decline. Results: Higher vascular risk and elevated Aβ burden interacted to predict more severe atrophy in frontal and temporal lobes, thalamus, and striatum. Higher Aβ burden, but not vascular risk, was associated with more severe atrophy in parietal and occipital lobes, as well as the hippocampus. Adjusting for diffusion- and FLAIR-based markers of white matter injury had little impact on the above associations. Gray matter atrophy mediated the association between vascular risk and cognitive decline at higher levels of Aβ burden. Discussion: We observed an interaction between elevated vascular risk and higher Aβ burden with longitudinal brain atrophy, which in turn influenced cognitive decline. These results support vascular risk factor management as a potential intervention to slow neurodegeneration and cognitive decline in preclinical Alzheimer disease.